Pain in the elderly with a cognitive deficit - Luca Ottolini (Publiediting, 2006)
Due to its high prevalence (45-80%) chronic pain in the elderly can be considered a social disease. Studies show that antalgics are prescribed less in demented patients with respect to non demented patients of the same age that suffer from similar pathologies that are potentially algogenic, which is proportional to an excessive prescription of neuroleptics and sedatives. The instruments that are used to self-evaluate pain in an elderly person, even those patients that have a slightly moderate cognitive deterioration, do not differ from those used for a young person. For serious cases of dementia, "etero-evaluation instruments" have been created. he objective of this revision of literature is not only the technical clarification of the state in which this field deals with, but to focus the attention, stimulate the sensibility of those that observe and to help to "translate" signals that might otherwise remain indecipherable or worse yet, interpreted in an incorrect manner. This is the only way in which a correct response can be given to a request by those that do not have a voice.